Challenges in Designing Blended Learning: the Experience of the “Schools of Instructional Design” - E. A. Drugova; I. I. Zhuravleva; M. G. Aiusheeva (Высшее образование в России)
The concept of “blended learning” has been widely discussed in Russian higher education. However, there are different interpretations of the concept and its status is not completely clear in the Russian regulatory environment. Although the effectiveness of this mode of education has been repeatedly recognised, systematic measures for the introduction of blended learning by universities are not being implemented. One of the factors for the success of such an implementation is the high-quality instructional design for blended learning. Difficulties in instructional design use can lead to the abandonment of blended learning or the adoption of less efficient practices. This paper explores the challenges faced by representatives of Russian universities involved in designing and teaching courses in a blended mode during the COVID-19 pandemic. The method used in the study is an online survey which was conducted in 2020-2021. The respondents were participants in the professional development program “School of Instructional Design for Blended Learning”. The results of the study showed that the respondents’ professional deficits in the design of blended courses were associated with the development of new ways of designing and teaching, growth of the course quality and student-centeredness, and more efficient allocation of time resources and use of online tools. The development stage, which involves the creation or updating of digital learning resources, turned out to be the most challenging for designing. Most respondents used LMS but were not satisfied with the quality of its application; also, the majority faced the problem of retaining student engagement in blended learning. The respondents would like to improve their formative and summative assessment practices and strengthen the course quality assessment practices. Commitment to overcome the identified difficulties can contribute to the creation of more effective practice-oriented professional development programs on teaching the blended learning design for educators, instructional designers and academic advisors in Russian higher education, leading to an increase in its quality.